2010
DOI: 10.1007/s12042-010-9046-1
|View full text |Cite
|
Sign up to set email alerts
|

Lablab purpureus—A Crop Lost for Africa?

Abstract: In recent years, so-called ‘lost crops’ have been appraised in a number of reviews, among them Lablab purpureus in the context of African vegetable species. This crop cannot truly be considered ‘lost’ because worldwide more than 150 common names are applied to it. Based on a comprehensive literature review, this paper aims to put forward four theses, (i) Lablab is one of the most diverse domesticated legume species and has multiple uses. Although its largest agro-morphological diversity occurs in South Asia, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
113
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(149 citation statements)
references
References 59 publications
2
113
0
1
Order By: Relevance
“…It is cultivated either as a pure crop or intercropped with finger millet, groundnut, castor, corn, pearl millet or sorghum. Despite its importance as a multi-purpose crop and ability to withstand drought better than common bean and cowpea (Maass et al, 2010), and adapt to acidic (Mugwira and Haque, 1993) and saline soils (Murphy and Colucci, 1999), Dolichos bean truly qualifies as 'underutilized' crop as evidenced by limited efforts for its genetic improvement.…”
Section: Issn: 2319-7706 Volume 7 Number 01 (2018)mentioning
confidence: 99%
“…It is cultivated either as a pure crop or intercropped with finger millet, groundnut, castor, corn, pearl millet or sorghum. Despite its importance as a multi-purpose crop and ability to withstand drought better than common bean and cowpea (Maass et al, 2010), and adapt to acidic (Mugwira and Haque, 1993) and saline soils (Murphy and Colucci, 1999), Dolichos bean truly qualifies as 'underutilized' crop as evidenced by limited efforts for its genetic improvement.…”
Section: Issn: 2319-7706 Volume 7 Number 01 (2018)mentioning
confidence: 99%
“…The Lablab bean, (Lablab purpureus) also referred to as Dolichos lablab is one such legume. It belongs to a species of beans in the family Fabaceae that is native to Africa and was in existence in1500 BC (Maass et al, 2010). It is a drought tolerant legume, and is part of the staple foods for some communities in Africa and Asia (Kimani et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from using the grain, the immature pods can be used as vegetable while the crop residue after harvest serves as manure (National Research Council, 2006). In Australia and other places it is used as a forage and feed crop (Abeke et al, 2008;Maass et al, 2010)Furthermore legume seeds have been reported to be useful in the prevention and management of common metabolic diseases such as diabetes mellitus and coronary heart diseases (Mathers, 2002;Morris, 2003;Singhal, et al, 2014). The Lablab crop has been documented to exhibit diverse agro-morphological characteristics and to be one of the most versatile legumes in the tropics (Maass et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations